Changes in BMI and Management of Patients with Childhood Onset Growth Hormone Deficiency in the Transition Phase - Bazarra-Castro, M. Á.; Sievers, C.; Schwarz, H. P.; Pozza, S.B.-D.; Stalla, G. K. (Experimental and Clinical Endocrinology & Diabetes, 2012)
We aimed at evaluating BMI changes during GH therapy pause, to assess the transfer pattern between children and adult medical services in our clinic and to confirm the previous growth hormone deficiency (GHD) diagnosis.Retrospective cohort study.We identified 75 transition patients (age at first visit <25 years) with pituitary deficiency (ICD-10:E.23) and GHD referred to our clinic between 2000–2009.Out of 75 patients with GHD (45 males, 30 females), 20 subjects suffered from an idiopathic GHD (iGHD) and 55 from an organic GHD (oGHD). During the GH therapy pause (26.4±34.8 months), we observed a significant BMI increase (23.6±4.4 to 27.1±7.2, p=0.02). Most males with iGHD discontinued endocrinologic control and GH substitution completely (5 patients out of 20) or after the first contact (3 patients out of 20). Most females with GHD continued medical control after transferral (22 patients). We retested 34/75 patients with GHD (45.3%). The preferred test was the growth hormone-releasing hormone-arginine (GHRH-arginine) (20/34 patients, 58.9%), followed by the insulin hypoglycemia test (IHT) alone (9 patients). 4 patients received both, the GHRH-arginine and the IHT. Seven retested patients with iGHD (63.6%) and all oGHD retested patients were still deficient.Our results provide information on negative effects of the discontinuation of GH treatment during the transition phase and should help to improve the compliance with treatment in this group of patients. Paediatric and adult endocrinologists participating together in a transition programme should emphasize on the positive effect of GH substitution in adulthood. Efforts should be made to particularly improve the transferral of male adolescents with iGHD, since they seem to escape medical care.
Keywords: hypopituitarism; pituitary adenoma; obesity